A Trajanic denarius from a modern grave in Inowrocław and the possibilities of its interpretation - Jarzęcki, Krzysztof (Acta Archaeologica Lodziensia, 2022)
The article is devoted to the interpretation of a 16th-17th century burial of a woman discovered in Inowrocław, who had a medallion made from a Trajanic denarius (RIC 6) placed around her neck. In one of the publications of this find it was stated that the owner wore the medal because she believed that it depicted the head of St. John the Baptist. According to written sources from the 16th and 17th centuries, the people in Poland called the Roman coins they found Saint John’s heads. In this article, such an interpretation is considered plausible, but it is not the only one. It is also possible that the medal was con sidered a beautiful item no matter what it depicted.